Predictors of suboptimal glycemic control in people with type 2 diabetes and overweight or obesity: insights from baseline analysis of a diabetes-specific meal replacement study - Chen, Lew Leong; Tohit, Noorlaili Mohd; Ludin, Arimi Fitri Mat; Manaf, Zahara Abdul; Shahar, Suzana (Frontiers in Nutrition, 2026)
BackgroundIndividuals with obesity and type 2 diabetes (T2D) constitute a high-risk subgroup that frequently exhibits suboptimal glycemic control even under standard management strategies. This study aimed to characterize the baseline metabolic and sociodemographic profiles of participants enrolled in a randomized controlled trial evaluating the efficacy of a diabetes-specific meal replacement (DSMR), and to identify predictors of suboptimal glycemic control.MethodsA total of 156 adults with T2D and BMI ≥ 25 kg/m2 were recruited from a primary care clinic. Participants were randomized to receive either DSMR plus dietary consultation or dietary consultation alone for 12 weeks, followed by a 12-week monitoring period. Participants in treatment group replaced one meal per day for 5 days a week. Baseline assessments included anthropometric measurements, biochemical markers, dietary intake, physical activity, and quality of life. Pearson correlation and blockwise logistic regression were used to explore predictors of suboptimal glycemic control (HbA1c ≥ 8.0%). This study has obtained human ethics approval from RECUKM (JEP-2019-566) and is registered at the Thai Clinical Trials Registry (TCTR ID: TCTR20210921004).ResultsThe cohort had a mean age of 52.2 years and mean HbA1c of 8.52%, indicating suboptimal glycemic control. While no correlation was found between BMI and HbA1c, HOMA-IR and ALT were positively associated with suboptimal glycemic status. In the final regression model, HOMA-IR (OR = 1.099, p = 0.024), ALT (OR = 1.025, p = 0.022), and diabetes duration (OR = 1.119, p = 0.035) were significant predictors, while total protein and ALP were inversely associated.ConclusionElevated insulin resistance and liver-related markers were independent predictors of suboptimal glycemic control. The result underscores the importance of targeting metabolic dysfunction beyond weight alone in interventions for high-risk T2D populations. These findings also support the mechanistic rationale for targeted nutrition-based strategies aimed at improving insulin sensitivity and hepatic function. Moreover, they provide valuable context for interpreting participant responses within the ongoing trial. The DSMR used in this trial may offer a viable and sustainable option to improve glycemic control among high-risk individuals with T2D.Clinical trial registrationhttps://www.thaiclinicaltrials.org/show/TCTR20210921004, TCTR20210921004.